2019
DOI: 10.5267/j.msl.2019.2.010
|View full text |Cite
|
Sign up to set email alerts
|

The triangular relationship between TQM, organizational excellence and organizational performance: A case of Arab American University Palestine

Abstract: The primary objective of the present study was to examine the impact of total quality management (TQM) practices on the performance of organization performance of Arab American University Palestine. The study was also interested in examining the role of organizational excellence in organizational performance and also investigated the impact of organizational excellence in the relationship between TQM practices and organizational performance. To achieve the objective of the current study, we employed the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 39 publications
3
34
0
3
Order By: Relevance
“…Same with the communication data, start from connections between two computers to computer networks [2]. The computer networks are an indispensable service [3].…”
Section: Revised Manuscript Received On July 22 2019mentioning
confidence: 99%
“…Same with the communication data, start from connections between two computers to computer networks [2]. The computer networks are an indispensable service [3].…”
Section: Revised Manuscript Received On July 22 2019mentioning
confidence: 99%
“…The system approach to the procedure defines the system as follows: "A system is a network of procedures that are interconnected, gathered together to carry out a certain activity or purpose" [9]. While the system approach to its component or element defines the system as follows: The system is the elements that interact with each other and are interconnected to achieve and to form one unit [10].Decision support system is a system helping in the analysis of business information [11].…”
Section: Systemmentioning
confidence: 99%
“…The system can be defined as a group of integrated elements with the same intend to achieve a goal [1]. The system is a collection of things or activities or sub-system elements that work together or connected in certain way to form a unity to carry out a function to achieve a goal [2]. The system can be defined as an entity or unit consisting of two or more components or subsystems (smaller systems) that are interconnected and related to achieve a goal [2].…”
Section: A the Definition Of Systemmentioning
confidence: 99%
“…The system is a collection of things or activities or sub-system elements that work together or connected in certain way to form a unity to carry out a function to achieve a goal [2]. The system can be defined as an entity or unit consisting of two or more components or subsystems (smaller systems) that are interconnected and related to achieve a goal [2]. From the three system definitions above, it can be concluded that the system is a set of elements that are interconnected with the same intention to achieve a particular goal [3].…”
Section: A the Definition Of Systemmentioning
confidence: 99%